PECULIARITIES OF PRE-CAMBRIAN AND PHANEROZOIC GRANITE-GNEISS STRUCTURE-FORMATION - SHEVCHUK, V.; SHEVCHUK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Different style of Archean, Proterozoic and Phanerozoic granite-gneiss structure-formation is argued. It caused by changes of thicknesses, thermal and rheologic regimes of lithosphere. Intermediate character of structural demonstration of Paleoproterozoic granite-formation with development of granite-gneiss monocline have been analyzed.